Emotion regulation in heavy smokers: experiential, expressive and physiological consequences of cognitive reappraisal - Wu, Lingdan; Winkler, Markus H.; Wieser, Matthias J.; Andreatta, Marta; Li, Yonghui; Pauli, Paul (Frontiers in Psychology, 2015)
Emotion regulation dysfunctions are assumed to contribute to the development of tobacco addiction and relapses among smokers attempting to quit. To further examine this hypothesis, the present study compared heavy smokers with nonsmokers in a reappraisal task. Specifically, we investigated whether nondeprived smokers and deprived smokers differ from nonsmokers in cognitive emotion regulation and whether there is an association between the outcome of emotion regulation and the cigarette craving. Sixty-five participants (23 nonsmokers, 22 nondeprived smokers, and 20 deprived smokers) were instructed to down-regulate emotions by reappraising negative or positive pictorial scenarios. Self-ratings of valence, arousal and cigarette craving as well as facial electromyography and electroencephalograph activities were measured. Ratings, facial EMG, and EEG data indicated that both nondeprived smokers and deprived smokers performed comparably to nonsmokers in regulating emotional responses via reappraisal, irrespective of the valence of pictorial stimuli. Interestingly, changes in cigarette craving were positively associated with regulation of emotional arousal irrespective of emotional valence. These results suggest that heavy smokers are capable to regulate emotion via deliberate reappraisal and smokers’ cigarette craving is associated with emotional arousal rather than emotional valence. This study provides preliminary support for the therapeutic use of reappraisal to replace maladaptive emotion-regulation strategies in nicotine addicts.